Future perspectives on outdoor recreation in Finland. Issue 4 (2nd October 2018) - Neuvonen, Marjo; Riala, Maria; Nummelin, Tuomas; Sievänen, Tuija; Tuulentie, Seija
ABSTRACT: The purpose of this study was to identify the different driving forces in society and trends in outdoor recreation to capture insights and improve understanding of the alternative futures of nature-based recreation and tourism in Finland. Professionals in recreation resources management, sport, land use, and forestry planning ( n = 38) were invited to discuss the future of nature-based recreation and tourism in three workshops in 2015. The workshops consisted of prematerial gathered with mind map, structured discussions, and the use of futures table method. Ten alternative descriptions of futures were created, with the time perspective being 2030. The future needs for recreation are expected to be more diversified and the population more polarised in terms of the time and money available for recreation. The outcomes suggest the need to support equality of access to nature and as a consequence the fair distribution of health and well-being benefits from nature.